THE DETECTION AND IDENTIFICATION OF THE CR1-LIKE MEMBRANE BINDING PROTEIN OF PORCINE ERYTHROCYTES - Zheng Zhang; Kuo-Hai Fan; Na Sun; Pan-pan Sun; Yao-Gui Sun; Hong-quan Li; Wei Yin (Journal of Animal and Plant Sciences, 2024)
Erythrocyte complement receptor I-like (ECR1-like) is a natural immunoreactive molecule on the surface of porcine erythrocyte membrane. The aim of this study was to establish an effective method for the detection and characterization of porcine erythrocyte CR1-like membrane-bound proteins, and to explore their expression characteristics and biological significance in porcine erythrocyte membranes.The CR1-like protein ligands were observed by laser confocal microscopy using fluorescence immunocytochemistry with two types of PDZ-binding domain monoclonal antibodies, FAP-1 (Fas-associated phosphatase-1) and ZO2 (Tight Junction Protein ZO-2); meanwhile, immunoprecipitation and Western blot techniques were used to detect the membrane proteins of porcine blood cells. The immunofluorescence cytochemical staining showed that the specific fluorescence sites of CR1-like and FAP-1 molecules in the porcine erythrocyte membrane skeleton were identical; the sum of the difference squares of the site distances of 253 typical positive erythrocytes was 0.2224, indicating that the difference between the site distances of CR1-like and FAP-1 in each group was approximately 0. The results showed that the distribution of CR1-like and FAP-1 was consistent with a co-local relationship, and the FAP-1 molecule was clearly observed in the examined gel by immunoprecipitation. The results indicate that CR1-like does not bind directly to the erythrocyte membrane skeleton protein, but is distributed on the surface of the porcine erythrocyte membrane through the riveted structure of the FAP-1 protein molecule.
Keywords: CR1-like; FAP-1; Immunoadhesion; Porcine erythrocytes